Creative Tourism Development from Cultural Identity and Diversity of Natural Resources Case of Sukon Island, Palian District, Trang Province - Junead, Jutatip; al, et (Journal of Cultural Approach, 2019)
The objectives of this study were to study the potential to analyze of cultural identity and diversity of natural resources and guidelines for creative tourism development from cultural identity and diversity of natural resources case of Sukon island, Palian district, Trang province. The researchers were used in–depth interview, and participant observation as a qualitative research instrument to understand the perspective of 100 stakeholders related to creative tourism who had been selected by purpose selection, snowball selection technique and survey tourism resources. SWOT analysis and content analysis were also used for the data analysis method. Diversity index analysis and equality index analysis by the t–test and one–way analysis of variance. The result of research found that in Sukon island, Palian district, Trang province of tourism resources such as natural resources, cultural and traditional resources, festival The result of research found that in Sukon island, Palian district, Trang province of tourism resources such as natural resources, cultural and traditional resources, festival resources, and important phenomena, there are outstanding activities resources and services including the facilities that support a creative tourism. However, the guideline for creative tourism development was identified as six aspects in order to develop the potential of creative tourism which comprises a tourist attraction, accessibility, facilities, touristic activities and tourism management, accommodation and activity.